Thực trạng và giải pháp ứng dụng AI trong việc nâng cao kĩ năng khẩu ngữ cho sinh viên ngành Trung Quốc học tại Trường Đại học Khoa học - Đại học Thái Nguyên - Nguyễn Văn Tiến, Nguyễn Văn Tiến; Phạm Chiến Thắng, Phạm Chiến Thắng (Tạp chí Giáo dục, 2026)
The rapid development of artificial intelligence (AI) in higher education has opened up new opportunities for foreign language teaching, especially oral Chinese skills. This study was conducted to analyze the current state of oral language training among students at the University of Science - Thai Nguyen University and propose a system of appropriate and effective AI-based solutions. A survey of 120 students revealed that the majority of learners face difficulties with pronunciation and intonation, lack confidence in communication, and lack a real-world speaking practice environment. The study also proposes five groups of AI-based solutions: 1 - using speech recognition technology (ASR) to correct pronunciation and intonation; 2 - applying large language models (LLM) to simulate conversations and increase opportunities for communication practice; 3 - personalizing speaking practice paths based on error analysis for each student; 4 - integrating AI into classroom teaching activities to increase the effectiveness of support and feedback; 5. Develop an AI-based oral assessment system based on the HSKK standard. These solutions not only help overcome existing limitations but also open up a new approach to personalized Chinese oral skills training, enhancing practice and effectively utilizing technology.